2015
DOI: 10.4244/eijy15m01_10
|View full text |Cite
|
Sign up to set email alerts
|

Use of a balloon-expandable transfemoral sheath in a TAVI cohort with complex access site - a propensity score matched analysis

Abstract: The use of a balloon-expandable large-bore sheath in patients with a high risk for vascular complications due to complex access-site anatomy proved to be feasible and safe. However, circumferential calcifications and sheath-to-artery ratios account for vascular access complications even in patients treated with the balloon-expandable sheath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our clinical practice, additional contralateral angiography and puncture into the pigtail (bull's eye technique) is the standard approach to ensure anterior puncture of the artery during the procedure. Furthermore, the use of dedicated transfemoral access sheaths in high-risk cohorts 27 and modern closure devices, 28 as well as alternative approaches such as transapical access or direct aortic TAVI, should be taken into consideration when transfemoral TAVI is limited or deemed risky.…”
Section: Stent Graft Placement For Asarvimentioning
confidence: 99%
“…In our clinical practice, additional contralateral angiography and puncture into the pigtail (bull's eye technique) is the standard approach to ensure anterior puncture of the artery during the procedure. Furthermore, the use of dedicated transfemoral access sheaths in high-risk cohorts 27 and modern closure devices, 28 as well as alternative approaches such as transapical access or direct aortic TAVI, should be taken into consideration when transfemoral TAVI is limited or deemed risky.…”
Section: Stent Graft Placement For Asarvimentioning
confidence: 99%
“…Second, during the post-expanded phase, the sheaths will be deformed and will lack the initial smooth surface and size. Complete recoil to the initial smaller calibre could lead to a situation that the arterial cut is larger than the introducer, with the risk of bleeding around the sheath 111 115 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, the PARTNER trial presented data which showed comparable results of the first generation Edwards Sapien THV (Edwards Lifesciences Co., Irvine, CA, USA) and SAVR for severe aortic stenosis in high-risk patients regarding mortality, reduction in symptoms and valve hemodynamics [ 3 ]. Despite introduction of a wide variety of THVs into the medical sector, with largely favorable results [ 4 , 5 ] and improved delivery systems, imaging or access site techniques [ 6 8 ], one major problem of THVs remains paravalvular leakage (PVL). PVL has a significantly higher incidence following TAVI compared to SAVR and leads to increased mortality if grade of PVL is ≥ moderate (2-year mortality of 30 % in mild aortic regurgitation, 40 % in moderate, 3-year mortality of 60 % in severe aortic regurgitation) [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%